2015
DOI: 10.1016/j.fgb.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans Yap1 is required for normal fluconazole and oxidative stress resistance

Abstract: Cryptococcus neoformans is a pathogen that is the most common cause of fungal meningitis. As with most fungal pathogens, the most prevalent clinical antifungal used to treat Cryptococcosis is orally administered fluconazole. Resistance to this antifungal is an increasing concern in treatment of fungal disease in general. Our knowledge of the specific determinants involved in fluconazole resistance in Cryptococcus is limited. Here we report the identification of an important genetic determinant of fluconazole r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 63 publications
2
32
0
2
Order By: Relevance
“…Nevertheless, the contradictory functions of AaTrr1 and AaGlr1 in response to mancozeb highlight the complexity of cellular resistance to any given fungicide. Cellular resistance to both oxidative stress and fluconazole mediated by the bZip transcription regulator Yap1 has also been reported in animal fungal pathogens (46,47).…”
Section: Figmentioning
confidence: 94%
“…Nevertheless, the contradictory functions of AaTrr1 and AaGlr1 in response to mancozeb highlight the complexity of cellular resistance to any given fungicide. Cellular resistance to both oxidative stress and fluconazole mediated by the bZip transcription regulator Yap1 has also been reported in animal fungal pathogens (46,47).…”
Section: Figmentioning
confidence: 94%
“…Although we have not found any reports on anecdotal clinical cases of VRC-resistant and ITCsusceptible A. flavus strain so far, we are concerned with whether the VRC-resistant A. flavus obtained in this study can emerge and prevail in clinical settings. We indicated the presence of a novel VRC resistance mechanism caused by a mutant of the Yap1 transcriptional factor, which has been studied as a major regulator of the oxidative stress response in S. cerevisiae, C. albicans, C. glabrata, Cryptococcus neoformans, and A. fumigatus (42)(43)(44)(45)(46)(47)(48)(49)(50)(51). We found that genes having the putative YRE, such as atrF, dsba, and gst, were upregulated in the Yap1 L558W strain.…”
Section: Discussionmentioning
confidence: 95%
“…Gene expression levels of efflux transporters and possible Yap1 regulating genes. Yap1 has been known as the major regulator of responses to reactive oxygen species (ROS) stress in S. cerevisiae and pathogenic fungi (42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Based on previous studies of S. cerevisiae (52)(53)(54)(55)(56)(57), the Leu558 residue in the A. flavus Yap1 is considered a key residue of the nuclear export signal (NES) that controls nuclear localization of Yap1.…”
Section: Whole-genome Sequencing Analysis Of Vrc-resistant a Flavusmentioning
confidence: 99%
“…Interestingly, AP-1-like factors have been found to be dispensable for the virulence of the human fungal pathogens Aspergillus fumigatus (85), Cr. neoformans (86), and C. albicans (82, 87), but are required for the virulence of a number of plant pathogens (8890). …”
Section: Adapting To Individual Stressesmentioning
confidence: 99%